The algorithmics of solitaire-like games - Backhouse, Roland; Chen, Wei; Ferreira, João F. (Elsevier, 2012)
One-person solitaire-like games are explored with a view to using them in teaching algorithmic problem solving. The key to understanding solutions to such games is the identification of invariant properties of polynomial arithmetic. We demonstrate this via three case studies: solitaire itself, tiling problems and a novel class of one-person games.